People First, Communication First: Public Relations For Information And Document Managers - Mehmet Ali Akkaya (Türk Kütüphaneciliği)
Communication for human is one of the most important tools for making life easier. A healthy communication is at the same time one of the needs for taking pleasure of life. Because; the human nature is based on living together with other people. Ability of understanding the other person and expressing oneself to the other one facilitates the way to the happiness and success for the individual first and then society of which he is a part. In case of a profession and its professionals, communication is not only the best facilitator for the workers but also for the success and prestige of the profession. Yılmaz who plays a part among the most productive members of profession, academicians, philosophers… of the knowledge and document management area in our country; together with his natural talent on the communication concern; once again invites us to think widely regarding ourselves, our profession, target audience and environment and freshen ourselves on these concerns via his second edition book with the heading as “First Human, First Communication”.